2023
DOI: 10.3390/ijms24043411
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Assisted Meta-Analysis of the Frequency of ACE I/D Polymorphisms in Centenarians and Other Long-Lived Individuals

Abstract: Current research on the angiotensin-converting-enzyme (ACE) gene has yielded controversial results on whether different ACE polymorphisms are linked with human longevity. ACE polymorphisms are a risk factor for Alzheimer’s disease and age-onset diseases that may contribute to the mortality of older people. Our goal is to consolidate existing studies, using artificial intelligence-assisted software to come to a more precise understanding of the role of the ACE gene in human longevity. The I (insertion) and D (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…A survivor or recruitment bias due to II males having died or been too frail to participate is unlikely given the body of literature indicating the association of the D allele with both morbidity and mortality [56][57][58][59][60][61][62]. However, although comparison with published UK studies where the individuals had average age over 75 did not affect our results, a recent meta-analysis of studies including centenarians, and older individuals as well as younger controls suggests a survivor advantage for DD individuals but not for ID individuals [63]. For this bias to account for our findings on the disproportionate number of DD men, the survivor effect would need to be greater and/or observed earlier in men as our observation of increased DD individuals was restricted to men.…”
Section: Discussionmentioning
confidence: 68%
“…A survivor or recruitment bias due to II males having died or been too frail to participate is unlikely given the body of literature indicating the association of the D allele with both morbidity and mortality [56][57][58][59][60][61][62]. However, although comparison with published UK studies where the individuals had average age over 75 did not affect our results, a recent meta-analysis of studies including centenarians, and older individuals as well as younger controls suggests a survivor advantage for DD individuals but not for ID individuals [63]. For this bias to account for our findings on the disproportionate number of DD men, the survivor effect would need to be greater and/or observed earlier in men as our observation of increased DD individuals was restricted to men.…”
Section: Discussionmentioning
confidence: 68%
“…For these reasons, it is important to assess interactions among genes and variants to define different phenotypes. This study using GSGA provides a general overview of major pathways as a blueprint of hallmarks relevant to phenotypic and disease ontology (e.g., AD, aging, and longevity in this study), while a personalized genetic overview, or direct-to-consumer genetic application for the assessment of health risks, would require a multidimensional analysis with genetic contributions of variants, epistatic effects, phenotypic and disease ontology, and other nongenetic effects in an individual [ 8 , 97 , 98 , 99 , 100 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2) There are genes with controversial phenotypic effects [ 97 ]. The prediction has been supported by the observation that the genetic network and epistasis analysis estimates genetic effects better than single-gene effects [ 8 , 97 , 101 ].…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are conflicting results among a number of studies that addressed the effects of different ACE variants on human life duration. To settle this issue, a very recent work used an artificial intelligence‐assisted meta‐analysis to investigate the contribution of the ACE gene to human longevity (Li & Murakami, 2023 ) which confirmed that the D/D genotype is positively associated with extreme longevity, whereas the I/I genotype is negatively associated with the latter trait.…”
Section: The Renin–angiotensin Systemmentioning
confidence: 99%